EARLY SOMATIC EMBRYOGENESIS AND SYNTHETIC SEED PREPARATION IN TAVERNIERA CUNEIFOLIA (ROTH) ARN. FOR CONSERVATION OF ROOT CULTURES - VITHAL AWAD,; ANIKET KUVALEKAR,; ABHAY HARSULKAR, (International Journal of Pharma and Bio Sciences, 2015)
Root explants of Taverniera cuneifolia (Roth) Arn., were studied for differential responses to various growth hormones. Auxins like Indole 3-acetic acid (IAA) stimulated multiple root induction, while 1-Naphthaleneacetic acid (NAA) induced tufts of roots along with calli. Cytokinins like Thidiazuron (TDZ) promoted release of cells resulting in cell suspension. Interestingly, treatment of Benzyl amino purine (BAP) produced direct somatic embryos (SE) within four weeks. We noticed maximum SEs (55.22±2.38 SE/ml) at 1.5 mg/l BAP as against control (3.88±1.96 SE/ml). The released SEs are encapsulated in sodium alginate beads to form synthetic seeds, which remained viable beyond three months. It was further noticed that encapsulated embryos preferentially produced vigorously growing roots (Root: 16.4±1.59, Plantlets: 2.88±1.05), whereas un-encapsulated SEs produced significantly more shoots, which regenerated into plantlets (Plantlets: 14.44±1.42, Roots: 4.66±1.32). This feature could be exploited for conservation for root clones that can potentially be used for GA production.